The specific character of hospitalization in a gynaecology ward = Specyfika hospitalizacji w oddziale ginekologii - Czerwiak, Grażyna; Adamczyk-Gruszka, Olga; Gruszka, Jakub (Journal of Education, Health and Sport, 2016)
Czerwiak Grażyna, Adamczyk-Gruszka Olga,Gruszka Jakub. The specific character of hospitalization in a gynaecology ward = Specyfika hospitalizacji w oddziale ginekologii. Journal of Education, Health and Sport. 2016;6(2):244-254. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46655 http://ojs.ukw.edu.pl/index.php/johs/article/view/3389 https://pbn.nauka.gov.pl/works/717121 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016. The specific character of hospitalization in a gynaecology ward Specyfika hospitalizacji w oddziale ginekologii Grażyna Czerwiak1, Olga Adamczyk-Gruszka2,Jakub Gruszka3 1 dr n. med. Grażyna Czerwiak: Zakład Umiejętności Pielęgniarskich i Organizacji Pracy, Instytut Pielęgniarstwa i Położnictwa Wydział Nauk o Zdrowiu Uniwersytetu Jana Kochanowskiego w Kielcach Kierownik Zakładu Umiejętności Pielęgniarskich i Organizacji Pracy: Prof. zw. dr hab. Bogdan Chazan 25-317 Kielce Al. IX Wieków Kielc 1 Grażyna Czerwiak Ph.D.: Department of Nursing Skills and Labour Organization, Institute of Nursing and Midwifery, Faculty of Health Sciences The Jan Kochanowski University, Kielce, Poland Head of the Departament : Prof. Bogdan Chazan Ph.D. habil./ Department of Nursing Skills and Labour Organization, Institute of Nursing and Midwifery. 2 dr n. med. Olga Adamczyk–Gruszka Zakład Położnictwa, Ginekologii i Pielęgniarstwa Położniczo- Ginekologicznego Wydział Nauk o Zdrowiu Uniwersytetu Jana Kochanowskiego w Kielcach Kierownik Zakładu: Prof. zw. dr hab. n. med. Mariusz Bidziński 2 Olga Adamczyk–Gruszka PhD: Departament of Obstetrics Gynecology and Obstetric- Gynecological Nursing Faculty of Health Sciences, Jan Kochanowski University, Kielce, Poland Head of the Departament: Prof. Mariusz Bidziński DD,PhD 3 student Jakub Gruszka: II Wydział Lekarski, Warszawski Uniwersytet Medyczny Dziekan II Wydziału Lekarskiego: Prof. dr hab. n. med. Marek Kuch 3 student Jakub Gruszka: II Faculty of Medicine, Medical University of Warsaw, Poland Head of the Departament: Prof. Marek Kuch MD, PhD Streszczenie Wstęp Hospitalizacja wyzwala specyficzne emocje wynikające z problemów zdrowotnych i egzystencjalnych pacjenta jego rodziny. Choroba potęguje nasilenie przykrych stanów emocjonalnych. Celem badań było poznanie przeżyć kobiet podczas hospitalizacji w oddziale ginekologicznym. Materiał i metody Badania przeprowadzono w oddziale ginekologiczno- położniczym w Kielcach wśród 83 kobiet. Zastosowano metodę sondażu diagnostycznego z wykorzystaniem ankiety. Materiał poddano analizie, a istotność różnic zweryfikowano testem χ2 Wyniki Wśród kobiet wymagających interwencji ginekologicznych hospitalizacja wyzwalała zaburzenia emocjonalne.. Lęk podczas oczekiwania na badanie potwierdziło większość badanych. Większość kobiet obawiała się zabiegu operacyjnego i bólu oczekując profesjonalnej opieki i wsparcia psychicznego. Wnioski: Hospitalizacja w oddziale ginekologii wyzwala specyficzne stany emocjonalne wśród kobiet. Badania i zabiegi ginekologiczne postrzegane były jako sytuacje trudne. Słowa kluczowe: hospitalizacja kobiet, zabiegi ginekologiczne, stany emocjonalne. Summary Introduction Hospitalization releases specific emotions resulting from health and existential problems of a patient and their family. Disease enhances the intensity of unpleasant emotional states. The aim of the research was to investigate the experiences accompanying women during hospitalization in a gynaecology ward. Material and methods The research was carried out in the ward of gynaecology and obstetrics in Kielce among 83 women. The diagnostic survey with the use of questionnaire was used. The material was analysed and the significance of differences was verified with the use of χ2 test. Results Hospitalization released emotional disorders among women requiring gynaecological examination. The majority of respondents confirmed feeling fear while waiting for the clinical examination. Most women were afraid of surgery and pain. They expected professional care and psychological support. Conclusions: Hospitalization in a gynaecology ward releases specific emotional states among women. Examinations and gynaecological surgeries were seen as especially difficult situations. Keywords: hospitalization of women, gynaecological surgeries, emotional states.